New Testament foundations ; v.1 : a guide for Christian students - Martin, Ralph Philip (Grand Rapids, MI : Eerdmans, 1985)
Includes bibliographical references and indexes.
Contents: v. 1. The four Gospels
Keywords: Bible. -- introductions